Discipline enforcement through leadership and motivation - Eko Sunarso, Asep Suryana, Ipong Dekawati, Aan Komariah, (Opción, 2019)
This research aims to determine effects of leadership style and work motivation on employee work discipline. Approach in the research uses qualitative approach and inter-variable analysis using simple and multiple linear regressions. Results of the research show that leadership style has positive and significant effects on work discipline. In addition, work motivation has positive and significant effects on employee work discipline. Leadership style shows balance of employer and achievement of organizational objectives. To improve employee work discipline, employers can provide rewards for employees having high discipline and sanctions for discipline violation. Leaders assist employees facing difficulty in completing their works.